Sexuality and the unnatural in colonial Latin America - Tortorici, Zeb 1978- (University of California Press, 2016)
"Explores the history of illicit and alternative sexualities in Latin America's colonial and early national periods. Together the essays examine how 'the unnatural' came to inscribe certain sexual acts and desires as criminal and sinful, including acts officially deemed to be 'against nature'--sodomy, bestiality, and masturbation--along with others that approximated the unnatural--hermaphroditism, incest, sex with the devil, solicitation in the confessional, erotic religious visions, and the desecration of holy images. In doing so, this anthology makes important and necessary contributions to the historiography of gender and sexuality. Amid the growing politicized interest in broader LGBTQ movements in Latin America, the essays also show how these legal codes endured to make their way into post-independence Latin America"--Provided by publisher
Includes bibliographical references and index
Keywords: Geschichte 1500-1830; Sex / Latin America / History; Sex and law / Latin America / History; Sex / Latin America / Religious aspects / History; Sex crimes / Latin America / History; Latin Americans / Sexual behavior / History; Geschichte; Religion; Sexualität; Lateinamerika